An Efficient and Secured Communication Scheduling Networks by Encoder and Decoder Scheme using Error Correction Algorithm - Sasikumar.M.S.S, Narayanan.A.E (International Journal of Advanced Science and Technology, 2020)
We examine a communication arranging as well as remote evaluation issue inside a worst case situation involving a strategic adversary. The sensor is constrained by the amount of transmissions with time horizon. In case the sensor makes a decision to transmit, the observation is sent to the encoder, which then simply encodes and also sends the observation on the decoder. Overall, silence is maintained by the encoder and the sensor. The decoder is necessary to create a real time estimation on the express adjustable. The decoder, the encoder, and the sensor collaborate to reduce the amount on the communication expense towards the sensor. There’s additionally a jammer interfering together with the interaction in between the decoder and the encoder, by injecting an error control algorithm on the communication channel. Exposed to a few specialized assumptions, a error correction algorithm, that is actually threshold dependant towards the scheduler, and then piecewise affine for the decoder and the encoder is obtained by us. We also performed many experimental test via training set or dataset and achieved the communication level and security level on comparing with existing models.